(untitled) (Mustansiria Dental Journal, 2018)
Objectives: Odontogenic cysts are one of the commonest bone destroying lesions of the maxillofacial skeleton, with the inflammatory radicular cyst being the most common jaw cyst. Cell adhesion molecules are known to be essential mediators of white blood cell adhesion & extravasations during inflammatory & immune reaction. Materials & Methods: Twelve formalin-fixed, paraffin-embedded radicular cysts were studied using LSAB/HRP immunohistochemical technique. Results: ICAM-1 expression was significantly high in radicular cysts with high expression in inflammatory cells infiltrate & connective tissue cells in cyst wall in comparison to VCAM-1 expression. Conclusion: In conclusion, the identification of the nature of adhesion molecules & inflammatory mediators involved not only expanded our knowledge of the molecular mechanisms but also provided the basis for a new understanding of the inflammatory response & its role in tissue homeostasis.